Tenancy by the Entirety and the Value of Wealth Insurance for Entrepreneurs - Jeffrey Traczynski (Institute of Labor Economics (IZA), 2020)
This paper explores the willingness of entrepreneurs to pay for wealth insurance to protect personal assets in case of business failure and the impact of this strategy on small business operation decisions. I show that antidiscrimination laws allow married firm owners in half of U.S. states to choose between asset protection and having more collateral for business funding, allowing entrepreneurs to reveal their valuation for preserving personal assets at time of failure. I find that firm owners value asset protection offered by tenancy by the entirety laws at 900-1000 per year. Firms receive smaller loans when entrepreneurs use this form of ownership to reduce the personal costs of firm failure, but show no differences in hiring patterns or spending on risky projects. This strategy of preparation in case of failure appears to affect small businesses through the funding channel.
Keywords: K35; K36; L26; M13; 330; personal bankruptcy; tenancy by the entirety; revealed preference; entrepreneurship